Development of ELT in Nepal: An Overview - Khadka, Bishnu Kumar (Journal of NELTA, 2022)
English language teaching (ELT) journey in Nepal needs to be explored from its historical perspective as there is only few literature available in this area. In this respect, there is a need of analysing historical development of ELT from various dimensions in chronological order. Therefore, this paper aims at presenting an overview of the development in terms of the policies and practices of ELT reviewing and analysing the available literature collected from different sources. After analysing the data, the research claims that English language teaching has been an integral part of education system in Nepal from nursery to tertiary level as a subject and/or medium of instruction throughout the history. Furthermore, the trends of development of ELT in Nepal seem to continue both in its quantity and quality in future due to the increasing use of English in multiple sectors.